2010
DOI: 10.1080/01446193.2010.494680
|View full text |Cite
|
Sign up to set email alerts
|

Building a new supply chain position: an exploratory study of companies in the timber housing industry

Abstract: Innovation is an important source of growth for many companies. It is also challenging, as it may require that the companies build a new position in the supply chain. The literature is devoid of analysis of different ways to build such positions in the construction industry. The purpose here is to explore the challenges involved in implementing innovations that require companies to establish new positions in a construction supply chain. Three in‐depth case studies in the Swedish timber housing industry illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…In the construction sector, the uptake of new building solutions has been found to be challenging despite their perceived benefits (e.g., Carter 1967, Holt 2013. Traditions and patterns of behavior in the construction sector operations are also key factors likely to affect WMC market diffusion (Nordin et al 2010). In a recent study by Matinaro and Liu (2017), traditional organizational culture was found to be a key aspect hindering innovativeness and sustainability in the Finnish construction sector.…”
Section: Construction Sector As a Business Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the construction sector, the uptake of new building solutions has been found to be challenging despite their perceived benefits (e.g., Carter 1967, Holt 2013. Traditions and patterns of behavior in the construction sector operations are also key factors likely to affect WMC market diffusion (Nordin et al 2010). In a recent study by Matinaro and Liu (2017), traditional organizational culture was found to be a key aspect hindering innovativeness and sustainability in the Finnish construction sector.…”
Section: Construction Sector As a Business Systemmentioning
confidence: 99%
“…Increasing the share of WMC is hindered by the strong path dependencies of concrete building networks Gustavsson 2008, Hemström et al 2017). Furthermore, Nordin et al (2010) concluded that re-structuring WMC business networks could partly solve the issue of a narrow WMC niche. According to Nordin et al (2010), re-structuring comprises changing both internal (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nordin et al (2010), re-structuring and intensifying of business cooperation is needed to break free from a niche level of WMC. This would essentially comprise changing both internal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the general description of business models, one key aspect is the border between activities of the company and those of external parties. Research has here referred to how business models may be open or include border-spanning activities (Vanhaverbeke & Chesbrough, 2014), thus emphasizing the business model's connection to supply-chain decisions (Lambert et al, 1998;Nordin et al, 2010) in how the business model includes make-or-buy decisions related to core and strategic competences of the firm.…”
Section: Business Modelsmentioning
confidence: 99%